Effects of seawater and freshwater challenges on the Gh/Igf system in the saline-tolerant blackchin tilapia (Sarotherodon melanotheron) - Link, Karl; Shved, Natallia; Serrano, Nabil; Akgül, Gülfirde; Caelers, Antje; Faass, Oliver; Mouttet, Farouhar; Raabe, Oksana; D’Cotta, Helena; Baroiller, Jean-François; Eppler, Elisabeth (Frontiers in Endocrinology, 2022)
Prolactin (Prl) and growth hormone (Gh) as well as insulin-like growth factor 1 (Igf1) are involved in the physiological adaptation of fish to varying salinities. The Igfs have been also ascribed other physiological roles during development, growth, reproduction and immune regulation. However, the main emphasis in the investigation of osmoregulatory responses has been the endocrine, liver-derived Igf1 route and local regulation within the liver and osmoregulatory organs. Few studies have focused on the impact of salinity alterations on the Gh/Igf-system within the neuroendocrine and immune systems and particularly in a salinity-tolerant species, such as the blackchin tilapia Sarotherodon melanotheron. This species is tolerant to hypersalinity and saline variations, but it is confronted to severe climate changes in the Saloum inverse estuary. Here we investigated bidirectional effects of increased salinity followed by its decrease on the gene regulation of prl, gh, igf1, igf2, Gh receptor and the tumor-necrosis factor a. A mixed population of sexually mature 14-month old blackchin tilapia adapted to freshwater were first exposed to seawater for one week and then to fresh water for another week. Brain, pituitary, head kidney and spleen were excised at 4 h, 1, 2, 3 and 7 days after both exposures and revealed differential expression patterns. This investigation should give us a better understanding of the role of the Gh/Igf system within the neuroendocrine and immune organs and the impact of bidirectional saline challenges on fish osmoregulation in other than osmoregulatory organs, notably the complex orchestration of growth factors and cytokines.